Planning and analysing 'Green' post-COVID-19 orthopaedic perioperative recovery pathway. Issue 4 (April 2021) - Iyengar, Karthikeyan P; Jain, Vijay K; Kariya, Ankur D
The effect of the severe acute respiratory syndrome coronavirus 2 pandemic on the National Health Service in the United Kingdom has been profound and unprecedented with suspension of most elective surgeries. As we are emerging from lockdown now, restarting elective surgical procedures in a safe and effective manner is an expected challenge. Many perioperative factors including patient prioritisation, risk assessment, health infrastructure and infection prevention strategies need to be considered for patient safety. The British Orthopaedic Association, along with the National Health Service, have provided recent guidelines for restarting non-urgent and orthopaedic care in the United Kingdom. In this article we review the current guidelines and literature to provide some clarity for clinical practice.